Algebraic solution of an anisotropic nonquadratic potential - Boschi-Filho, H. [UNESP]; Vaidya, A. N. (Elsevier B.V., 1990)
We show that an anisotropic nonquadratic potential, for which a path integral treatment has been recently discussed in the literature, possesses the SO(2, 1) ⊗SO(2, 1) ⊗SO(2, 1) dynamical symmetry, and construct its Green function algebraically. A particular case which generates new eigenvalues and eigenfunctions is also discussed. © 1990.